2018
DOI: 10.1126/sciadv.aat8712
|View full text |Cite
|
Sign up to set email alerts
|

A high-entropy alloy with hierarchical nanoprecipitates and ultrahigh strength

Abstract: HEAs’ compositional space allows the design of hierarchical microstructures that contribute to the exceptional strength values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(92 citation statements)
references
References 39 publications
1
91
0
Order By: Relevance
“…On the other hand, there was also small section of crack along coherent TBs which have higher fracture resistances than incoherent GBs. Therefore, TBs could increase the fracture resistances effectively [111][112][113][114][115][116][117][118][119][120][121][122]. Xiong et al have indicated that 316L stainless steels with bundles of nanoscale deformation twins have beneficial to enhance the fracture resistance [113,114].…”
Section: Fatigue and Damage Tolerancementioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, there was also small section of crack along coherent TBs which have higher fracture resistances than incoherent GBs. Therefore, TBs could increase the fracture resistances effectively [111][112][113][114][115][116][117][118][119][120][121][122]. Xiong et al have indicated that 316L stainless steels with bundles of nanoscale deformation twins have beneficial to enhance the fracture resistance [113,114].…”
Section: Fatigue and Damage Tolerancementioning
confidence: 99%
“…Precipitation strengthening is also considered to be an effective strengthening mechanism in HEAs. Fu dual-phase HEA that contains an FCC matrix (γ) with a small volume fraction of body-centered cubic (BCC) phase [118]. There are some primary nanoprecipitates γ and secondary nanoprecipitates γ* in FCC matrix.…”
Section: Nanoprecipitatementioning
confidence: 99%
See 2 more Smart Citations
“…

In the present study,asonochemical-based method for onepot synthesis of entropy-stabilized perovskite oxide nanoparticle catalysts with high surface area was developed. [7] Amongt his novel class of crystalline materials, high-entropy alloys were first reported in 2004 by the independentp ioneering works of Cantor et al and Yeh et al [5,6] Recent studies have extended the high-entropy concept to include the ionic compounds, in which five or more metallice lements have been used to populate as inglec ation sublattice to introduce highc onfigurational entropyi nto the crystal structure. Ta king advantage of the acoustic cavitation phenomenon in theu ltrasonication process, BaSr(ZrHf-Ti)O 3 ,B aSrBi(ZrHfTiFe)O 3 and Ru/BaSrBi(ZrHfTiFe)O 3 nanoparticles were crystallized as single-phase perovskite structures through ultrasonication exposure withoutc alcination.

…”
mentioning
confidence: 99%